Use of Class Fiber to Reinforce Ortohodontic Plates Against Mechanical Forces - İbrahim Erhan Gelgör; Bülent Çatalbaş (Galenos Yayinevi, 2006)
This study investigated the different effects of quantitative percentages of glass fiber intensity on the transverse strength and maximum deformation of orthodontic acrylic resin. Forty specimens were formed in a specially designed mold to produce identical specimens in accordance with the manufacturer's recommendations. Four different percentages of glass fiber reinforcements in loose random form were studied. Each glass fiber treatment percentage (0%, 1%, 2%, 5%) was related to the total powder/liquid mass. The results indicated that 2% glass fiber treatment enhanced the transverse strength of the tested specimen. Maximum deformation at failure in the tested treatment groups was found to be different. The interaction of glass fiber concentration on fracture strength and deformation was significant. In conclusion the 2% glass fiber concentration was found to yield optimum fracture strength and deformation results. Increased amount of glass fiber incorporation resulted in decreased mechanical properties of the resin.